The Social Bench : Interactive product design for public space - Järlehag, Ella (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
This report covers a master’s thesis project in industrial design engineering, product design, at Luleå University of Technology. The objective for the thesis has been to develop a product that enables interaction between people in the public space. This to promote meetings and create an additional experience with the help of integrated technology. Studies of concerned theories have been research which included information about interaction design, ubiquitous computing, public space and social innovation. It was decided early in the project to focus on benches as they are a natural part of public spaces like parks. To seek an understanding for the projects context an benchmark on similar projects, interviews with experts in choosing furniture for public space and a cultural probe has been conducted. This research served as a base for the design process which started with an ideation phase where creative methods were used to generate a great amount of ideas for possible interactions. Experience prototyping was one of the key methods used and when enough ideas had been developed four different concepts where put together that focused on how the interaction would be perceived. With the help of a voting process and a concept-scoring matrix one concept was chosen to further develop. This concept was then detailed design were the design for the actual bench was decided and two prototypes were built to be able to demonstrate and test the final concept. The final result of the thesis project was the interactive bench named The Social Bench. The Social Bench has integrated technology in the form of lightning and sensors that detect when someone sits down. This triggers the interaction and enables the user to choose the color on the light underneath the bench by sitting on the different colored seating disks placed on the bench. The bench is supposed to function in a network of benches that are all connected and mimics each other’s interactional patterns. This is displayed by the choosing of color were every users choice ...